Great Expectations and Hard Times: The (Nontrivial) Impact of Education on Domestic Terrorism. (October 2015) - Brockhoff, Sarah; Krieger, Tim; Meierrieks, Daniel
This contribution investigates the role of education in domestic terrorism for 133 countries between 1984 and 2007. The findings point to a nontrivial effect of education on terrorism. Lower education tends to promote terrorism in a cluster of countries where socioeconomic, political, and demographic conditions are unfavorable, while higher education reduces terrorism in a cluster of countries where conditions are more favorable. This suggests that country-specific circumstances moderate the effect of education on terrorism. The results of this study imply that promoting education needs to be accompanied by sound structural change to positively affect (individual and society-wide) development and consequently reduce terrorism.